EFFICIENCY OF PRE-PROSTHETIC PREPARATION OF THE ALVEOLAR PART OF THE MANDIBLE IN PATIENTS WITH PARTIAL ADENTIA - Stupnytskyi, I.R.; Stupnytskyi, R.M.; Lokes, K.P. (World of Medicine and Biology, 2023)
The tooth extraction leads to the development of horizontal and vertical atrophy of the alveolar process of the jaws. In approximately 90 % of cases, it is necessary to perform one or another type of bone augmentation. The purpose of this study was to study the effectiveness of the use of bone substitutes in the restoration of a tooth row defect after tooth extraction. The obtained results of a comparative study of the state of the optical density of bone tissue of the mandibular alveolar socket in patients at different stages of bone tissue reconstruction objectively proved the presence of a gradual increase in bone tissue density in the areas of application of osteoplastic materials. Densitometric indicators of patients were kept within the upper limit of average values (132±13, 147.2±24.34, 160.3±14.58 units).
Keywords: bone augmentation; tooth extraction; adentia; bone atrophy